Implementasi Peran Guru dalam Mengembangkan Kecerdasan Moral pada Siswa Kelas IV SDN Karawaci 1 Kota Tangerang - Nursiah, Nursiah; Sa’odah, Sa’odah; Nurfadhillah, Septy (Lembaga Yasin AlSys, 2022)
This research was conducted at SDN Karawaci 1 Tangerang City, which aims to find out how the role of teachers in developing moral intelligence in fourth grade students at SDN Karawaci 1 Tangerang City. Because students need not only academic achievement, they also need moral skills, especially when dealing with other people. This study uses a qualitative research approach. In addition to using a qualitative approach, the method used is descriptive qualitative. In this study, the subjects that became the focus of research were teachers and fourth grade students at SDN Karawaci 1. In this study, researchers used eleven 11 subjects consisting of 10 students and 1 teacher. The results of this study show that the role of the teacher here has been very active in contributing to its role, namely combining the values of moral intelligence that will be built on students with the learning process. In addition, the teacher also teaches students aspects of moral intelligence by doing it directly. Teachers are able to relate aspects of moral intelligence in the learning process with examples of teachers using methods that relate to the values of character education in the classroom, one of which is by using the role playing method. develop students' moral intelligence in the Learning Implementation Plan (RPP).